Novel hybrid materials: functionalized polyoxometalates as potential metalloligands - Mijares, Kristopher (Kansas State University, 2008)
Polyoxometalates are self-assembled metal-oxygen anionic clusters formed primarily by Mo, W and the Group V transition metals. Their structural, chemical and physical diversity have attracted much attention from fields such as catalysis, imaging, magnetic materials, medicine and photochromism. While many of these inorganic systems are easy to prepare, their conversion to hybrid inorganic-organic materials through functionalization is an ongoing challenge. Two approaches used for functionalization involve the insertion of metal-nitrido fragments into a lacunary polyoxometalate or the direct replacement of the terminal oxo ligands with the isoelectronic organoimido [NR][superscript]2-, hydrazido [NNR[subscript]2][superscript]2-, nitrosonium [NO][superscript]+ and diazenido [NNR][superscript]+ ligands. The later process has been proven successful with a variety of different nitrogenous ligands. One of our group's goals has been to synthesize a functionalized hexamolybdate species capable of metal coordination, with the ultimate goal of forming self-assembled networks. However, previous results have been unsuccessful due to the electron withdrawing effect of the cluster which is transmitted to the metal binding site. In order to overcome this effect, several new organoimido delivery reagents (phosphineimines, isocyanates and arylamines) containing electron donating substituents have been synthesized and characterized. Attempts to attach these species to hexamolybdate are described. The synthesis and characterization of biarylimido ligands bearing remote σ-donor functionalities and their incorporation into the hexamolybdate cluster will be described. A new and exciting avenue of polyoxometalate chemistry will be demonstrated through the successful metal coordination of the biarylimido functionalized hexamolybdate to a ruthenium(II) metalloporphyrin. This also brings the hexamolybdate polyoxometalate one step closer to being capable of forming the supramolecular architectures mentioned earlier. A chromium(V) nitrido polyoxometalate has been synthesized and characterized from a lacunary Keggin precursor, in collaboration with our colleagues in Paris. The ability of this complex as a nitrogen transfer reagent will be explored. An alternative synthetic route to the osmium-nitrido-Dawson species, [(OsN)P[subscript]2W[subscript]17O[subscript]61][superscript]4- will also be described. These nitrido species could be an entry point to other derivatives through reactions with various nucleophiles and electrophiles.
Keywords: polyoxometalates; hexamolybdate; functionalized; hybrid; keggin; Chemistry, Inorganic (0488)